2018
DOI: 10.1111/jfpp.13678
|View full text |Cite
|
Sign up to set email alerts
|

Modified atmosphere packaging and gamma-irradiation of some herbs and spices: Effects on antioxidant and antimicrobial properties

Abstract: Thyme, rosemary, black pepper, and cumin were packaged in 100% N 2 (MAP) or air (AP) and gamma-irradiated at 0, 6, or 14 kGy. The changes in antioxidant and antimicrobial activities of their essential oils and methanol extracts were determined. Irradiation decreased the total phenolic content of AP samples (except thyme). Irradiation increased the 2,2-diphenyl-2-picrylhydrazyl radical scavenging activity in thyme extract and cumin essential oil in AP, but it decreased the activity in cumin extract (MAP). Ferri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…There are some studies reporting the effects of gamma irradiation on the quality of thyme in literature. In accordance with our observation on the total phenolic content of thyme treated with UV‐C doses up to 205.6 J/cm 2 , Kirkin and Gunes () reported that the total phenolic content of thyme extracts was not affected by irradiation at 14 kGy. They also reported that the DPPH of thyme was increased significantly by irradiation at 14 kGy in aerobic packaged samples compared to the non‐irradiated control but not affected when irradiation was applied in modified atmosphere package.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…There are some studies reporting the effects of gamma irradiation on the quality of thyme in literature. In accordance with our observation on the total phenolic content of thyme treated with UV‐C doses up to 205.6 J/cm 2 , Kirkin and Gunes () reported that the total phenolic content of thyme extracts was not affected by irradiation at 14 kGy. They also reported that the DPPH of thyme was increased significantly by irradiation at 14 kGy in aerobic packaged samples compared to the non‐irradiated control but not affected when irradiation was applied in modified atmosphere package.…”
Section: Resultssupporting
confidence: 93%
“…Thyme is well known for its antioxidant properties. It is known that the high antioxidant activity of thyme is caused by phenolic TA B L E 1 Effects of different UV-C dose on total phenolic content and antioxidant capacity of thyme monoterpenes, thymol, and carvacrol, which are the major compounds found in thyme (Yanishlieva, Marinova, & Pokorný, 2006 Kirkin and Gunes (2018) reported that the total phenolic content of thyme extracts was not affected by irradiation at 14 kGy. They also reported that the DPPH of thyme was increased significantly by irradiation at 14 kGy in aerobic packaged samples compared to the non-irradiated control but not affected when irradiation was applied in modified atmosphere package.…”
Section: Total Antioxidant Activity and Phenolic Contentmentioning
confidence: 99%
“…[333] EOs can be used in the food industry also in synergy with irradiation and as reinforcement of modified atmosphere packaging techniques. The direct effect of gamma irradiation on EOs is up to now subject of discussion and some data on the impact of this practice on chemical composition and organoleptic descriptors was already published, [334,335] and it seems that the irradiation-induced changes in the quality depend on the atmosphere during the treatment. However, the combination of irradiation and coating containing EOs is an effective strategy to reduce microbial count in food with minimal impact on sensory properties which is worth investigating in the coming years.…”
Section: Uses Of Eos In the Food Industriesmentioning
confidence: 99%
“…Research on the freeze-drying process for fruits has been widely reported ( Lohachoompol et al., 2004 ; Giuffre et al., 2019 ), but no publications have been found that explain the physical and sensory characteristics of frozen strawberries produced from frozen vacuum dryers. Publications that have been revealed by previous researchers include engineering environmental storage to extend the shelf life of strawberry fruit ( Fernández-Lara et al., 2015 ), the combined effect of gamma irradiation and MAP on the antioxidant and antimicrobial properties of strawberries ( Kirkin and Gunes, 2018 ), evaluation of the effect of modified atmospheric packaging (MAP) on strawberry storage ( Peano et al., 2014 ), coating method to maintain the organoleptic and functional properties of strawberries ( Sicari et al., 2020 ), and effect of lemon verbena bio-extract on phytochemical and antioxidant capacity of strawberry fruit during cold storage ( Moshari-Nasirkandi et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%